2018
DOI: 10.1007/978-3-319-99704-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Logistics Route Selection Using AHP: A Case Study of Electronics Scrap from Pakistan

Abstract: Selection of optimal route among available choices in the presence of various factors has been a prime focus in logistics. In this paper, Analytical Hierarchy Process (AHP) is used for selection of optimum route among available options for revere logistics of electronics scrap from Pakistan to the industry using End of Life (EOL) products as there raw material. The main objective of this study is to find out the optimal reverse logistic path for electronic scrap considering: cost of transportation, time of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Waqas et al [16] have identified the critical factors of reverse logistics and its barriers to Pakistan's manufacturing industry. Mushtaq et al [17] studied reverse logistics route selection in the electronic industry of Pakistan. Waqas et al [18] found the impact of reverse logistics barriers on sustainable firm performance and took the case of Pakistan's manufacturing industry.…”
Section: Position Of Reverse Logistics In Pakistanmentioning
confidence: 99%
“…Waqas et al [16] have identified the critical factors of reverse logistics and its barriers to Pakistan's manufacturing industry. Mushtaq et al [17] studied reverse logistics route selection in the electronic industry of Pakistan. Waqas et al [18] found the impact of reverse logistics barriers on sustainable firm performance and took the case of Pakistan's manufacturing industry.…”
Section: Position Of Reverse Logistics In Pakistanmentioning
confidence: 99%
“…In addition, to assess the environmental impact of production systems, sub-criteria on emissions, certificates of environmental standards and environmentally friendly materials are introduced in the studies. As summarized in Table 2, several methods for alternative selection problems have been reported in the literature, almost the techniques in the literature are from the MCDM field, such as FAHP [5,14,15,18,[27][28][29][30][31][32][33][34][35][36][37][38][39][40], FANP [6,27,37,41], FTOPSIS [4,11,29,36,40,42,43], and others [6,18,24,35,43,44]. This problem may have been partly addressed by previous studies by DEA models [5,27,32,33,35,37] and mathematical optimization models [24,45].…”
Section: Literature Reviewmentioning
confidence: 99%